2021
DOI: 10.22541/au.161282021.11673088/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effect of the COVID-19 lockdown on children with asthma-related symptoms: A tertiary care center experience

Abstract: Background: Acute asthma exacerbations are a common cause for emergency department (ED) visits and hospitalizations in children. Since the outbreak of COVID-19 and the education system closure/ total lockdown in Israel on March 2020, we have noticed a decrease in pediatric ED visits and an increase in hospitalizations of asthma exacerbations. Objective: to examine the patterns of ED visits for asthma exacerbations during COVID-19 outbreak, in comparison to the previous year. Methods: a retrospective study comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
(27 reference statements)
0
9
0
Order By: Relevance
“…Curatola et al 15 found a 84% decrease in bronchiolitis cases in the ER. In addition, a positive effect on asthma control was found, with fewer ER visits 2,3 and fewer exacerbations 16,17 …”
Section: Discussionmentioning
confidence: 94%
“…Curatola et al 15 found a 84% decrease in bronchiolitis cases in the ER. In addition, a positive effect on asthma control was found, with fewer ER visits 2,3 and fewer exacerbations 16,17 …”
Section: Discussionmentioning
confidence: 94%
“…Ten studies, [14][15][16][17][18][19][20][21][22][23] with 22,159 subjects were included for the final meta-analysis. The sample size of the studies ranged from 16 to 18,912.…”
Section: Study Characteristicmentioning
confidence: 99%
“…Five studies 16,17,19,19,21,22 were included in this outcome. The metaanalysis showed that there was no significant difference between two groups in asthma admission (OR = 0.84, 95% CI = [0.32-2.20], Z = 0.36, p = 0.72) (Figure 3).…”
Section: Asthma Admissionmentioning
confidence: 99%
“…Several studies reported how social distancing and stepped‐up hygiene measures determined a concomitant reduction in the diffusion of respiratory pathogens, leading to decreased respiratory tract infections, 3,8,28–32 and identify it as the main factor. Moreover, increased adherence to controller medications among the asthmatic population during lockdowns was demonstrated 30,32,33 …”
Section: Discussionmentioning
confidence: 99%